PENGARUH INVESTASI DAN TENAGA KERJA TERHADAP PDB SEKTOR PERTAMBANGAN DI INDONESIA - Agus Sulaksono (Universitas Gunadarma, 2015)
Mining investment in Indonesia increased foreign exchange earnings for the country, the creation of jobs. Investment as the main driver and is the key in the concept of the economy and job creation and poverty reduction. This study was to determine the effect of investment, labor mining sector to the Gross Regional Domestic Product without Oil and Gas Mining Sector. The data used is secondary data, investment, labor and mining sector Gross Domestic Product Without Oil and Gas Mining Sector from 2000 to 2012. The analytical method used is regression analysis using SPSS 17.0.Based on the analysis we can conclude the mining sector investment has positive influence on the Gross Regional Domestic Product without Oil and Gas Mining Sector. The mining sector workforce has positive influence on the Gross Regional Domestic Product without Oil and Gas Mining Sector. Investment and mining sector workforce together a positive effect on the Gross Regional Domestic Product without Oil and Gas Mining in Indonesia. Keyword: Investment, Labor, Gross Domestic Product